Systematic comparison of adeno‐associated virus and biotinylated dextran amine reveals equivalent sensitivity between tracers and novel projection targets in the mouse brain. Issue 9 (15th June 2014) - Wang, Quanxin; Henry, Alex M.; Harris, Julie A.; Oh, Seung Wook; Joines, Kevin M.; Nyhus, Julie; Hirokawa, Karla E.; Dee, Nick; Mortrud, Marty; Parry, Sheana; Ouellette, Benjamin; Caldejon, Shiella; et al.
ABSTRACT As an anterograde neuronal tracer, recombinant adeno‐associated virus (AAV) has distinct advantages over the widely used biotinylated dextran amine (BDA). However, the sensitivity and selectivity of AAV remain uncharacterized for many brain regions and species. To validate this tracing method further, AAV (serotype 1) was systematically compared with BDA as an anterograde tracer by injecting both tracers into three cortical and 15 subcortical regions in C57BL/6J mice. Identical parameters were used for our sequential iontophoretic injections, producing injections of AAV that were more robust in size and in density of neurons infected compared with those of BDA. However, these differences did not preclude further comparison between the tracers, because the pairs of injections were suitably colocalized and contained some percentage of double‐labeled neurons. A qualitative analysis of projection patterns showed that the two tracers behave very similarly when injection sites are well matched. Additionally, a quantitative analysis of relative projection intensity for cases targeting primary motor cortex (MOp), primary somatosensory cortex (SSp), and caudoputamen (CP) showed strong agreement in the ranked order of projection intensities between the two tracers. A detailed analysis of the projections of two brain regions (SSp and MOp) revealed many targets that have not previously been described in the mouse or rat. Minor retrograde labeling of neurons was observed in all cases examined, for both AAV and BDA. Our results show that AAV has actions equivalent to those of BDA as an anterograde tracer and is suitable for analysis of neural circuitry throughout the mouse brain. J. Comp. Neurol. 522:1989–2012, 2014. © 2014 Wiley Periodicals, Inc.